ANALISIS YURIDIS SANKSI PIDANA KEKERASAN DALAM RUMAH TANGGA (KDRT) (NOMOR 369/PID.SUS/2020/PN MRE) - Rafli Novaldi; Dian Adriawan Dg. Tawang (Fakultas Hukum Universitas Trisakti, 2022)
DP369/Pid.Sus/2020PN Mre In the Judge's Decision continued the conversation with the Law on the Elimination of Domestic Violence that was hidden in Article 44 paragraph 1. The definition of Domestic Violence or what can be abbreviated as KDRT is an act of a person, especially a woman, which results in misery or suffering sexual, physical, neglect of the household and psychological. The issue at hand is how domestic violence's criminal sanctions will be based on the study of Decision No. 369/Pid.Sus/2020PN Mre and what the goals of the study are as stated in Law on the Elimination of Domestic Violence No. 23 of 2004. The normative juridical analysis technique is used and the rules governing it are examined. The judge gave the offender at least half of the maximum sentence allowed by Article 44 of the Constitution.